Rapid microarray-based assay for detection of pyrazinamide resistant Mycobacterium tuberculosis - Havlicek, Juliane (Diagn Microbiol Infect Dis, 2019)
Pyrazinamide (PZA) is a key antibiotic for the treatment of drug susceptible tuberculosis. PZA-resistance is mainly mediated by mutations in the pncA gene; however the current gold standard is a phenotypic drug susceptibility test requiring a well-adjusted pH-value for reliable results. Our melting curve assay detects a non-wild type genotype in selected pncA regions in at least 3750 gene copies/mL within 2.5 hours. The prototype assay was further evaluated by analyzing 271 Mycobacterium tuberculosis complex isolates from Swaziland originating from a previously published drug resistance survey and including 118 isolates with pncA mutations. Sensitivity was 83% (95% CI 75–89%) and specificity was 100% (95% CI 98–100%). Under consideration of further improvements with regard to the target range our melting curve assay has the potential as a rapid rule-in test for PZA susceptibility (wild type pncA), however false resistant results (mutant pncA, but PZA susceptible) cannot be ruled out completely.